Trapped Between Theological and Medical Notions of Possession: A Case of Possession Trance Disorder With a 3-Year Follow-Up - Pietkiewicz, Igor J.; Kłosińska, Urszula; Tomalski, Radosław (Frontiers in Psychiatry, 2022)
Few studies on Possession Trance Disorder (PTD) describe diagnostic and research procedures in detail. This case study presents the clinical picture of a Caucasian Roman-Catholic woman who had been subjected to exorcisms because of her problems with affect regulation, lack of control over unaccepted sexual impulses, and somatoform symptoms accompanied by alterations in consciousness. It uses interpretative phenomenological analysis to explore meaning attributed by her to ‘possession’ as a folk category and a medical diagnosis; how this affected her help-seeking was also explored. This study shows that receiving a PTD diagnosis can reinforce patients’ beliefs about supernatural causation of symptoms and discourage professional treatment. Dilemmas and uncertainties about the diagnostic criteria and validity of this disorder are discussed.